The type specimens of Corvidae (Aves) in the Museum für Naturkunde at the Humboldt-University of Berlin, with the description of a new subspecies of Dendrocitta vagabunda - Steinheimer, Frank D. (Zootaxa, 2009)
The status of all type specimens of crows, raven, jays, magpies, treepies, and choughs (Corvidae) housed in the Museum für Naturkunde at the Humboldt-University of Berlin (ZMB) is discussed, including those specimens considered to be paralectotypes and paratypes. Each entry includes the history of the specimen, and, when necessary, its nomenclature and taxonomy. A brief overview is given of the impact of World War II on the bird collections of ZMB. Nomenclatural changes were instituted in two species groups: Lophocitta ardesiaca Bonaparte, 1850, is synonymized with Platylophus galericulatus galericulatus (Cuvier, 1816), and Platylophus galericulatus malaccensis Cabanis, 1866, becomes the valid name for the birds from the Malayan Peninsula formerly known as Platylophus galericulatus ardesiacus (Bonaparte, 1850). The holotype of Crypsirhina pallida Blyth, 1846, formerly believed lost, was located and identified as a senior synonym of Dendrocitta vagabunda vernayi and must replace the latter for birds from south-eastern and eastern Central India. This leaves the West and western Central Indian population of D. vagabunda unnamed for which a new subspecies name is proposed.